Sealing material for display device, sealing material, organic el display, and LED display
By using epoxy resin, thermal acid initiator and phosphor in the sealing material of the image display device, controlling the fluorine ion weight or using specific quaternary ammonium salts as thermal acid initiators, the discoloration of the sealing material under high temperature and high humidity is solved. Problem, achieving stable display effect.
Patent Information
- Application Number
- CN202380051282.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-26
- Filing Date
- 2023-07-20
- Publication Date
- 2025-02-21
AI Technical Summary
In the image display device, the cured substance of the sealing material containing the phosphor is prone to discoloration under high temperature and high humidity, resulting in poor display effect.
A sealing material containing an epoxy resin, a thermal acid initiator and a fluorescent substance is used to control the amount of fluorine ions to be less than 100 ppm, or a quaternary ammonium salt with B(C6F5)4- as the counter anion is used as a thermal acid initiator , to inhibit discoloration of cured substances.
Under high temperature and high humidity conditions, the discoloration of the sealing material cured substance is effectively suppressed and the stability of the display effect is maintained.
Smart Images

Figure BDA0005221717880000041 
Figure BDA0005221717880000061 
Figure BDA0005221717880000062
Abstract
Description
Technical Field
[0001] The present invention relates to a sealing material for a display device, a sealing member, an organic EL display and an LED display. Background Art
[0002] In recent years, as an image display device including an optical element, for example, an organic EL display is known. In such an image display device, the optical element is sealed with a sealing layer in order to suppress degradation of the optical element due to moisture in the atmosphere or the like.
[0003] The sealing layer is formed by, for example, embedding the optical element in the sealing material for a display device and then curing the sealing material for a display device.
[0004] As such a display device sealing material, for example, an image display device sealing material containing an epoxy resin and a thermal cationic curing agent has been proposed (for example, refer to Patent Document 1).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2021 / 024616 Pamphlet Summary of the invention
[0008] Problems to be solved by the invention
[0009] On the other hand, in image display devices, color filters are provided to express colors on a screen. However, from the viewpoint of miniaturization, it is considered to mix a fluorescent substance in a sealing material for a display device instead of a color filter.
[0010] However, the cured product of the sealing material for a display device containing a phosphor has a disadvantage of discoloring under high temperature and high humidity.
[0011] The present invention provides a sealing material for a display device that suppresses discoloration under high temperature and high humidity, a sealing member including a cured product of the sealing material for a display device, an organic EL display including the sealing member, and an LED display including the sealing member.
[0012] Means for solving problems
[0013] The present invention [1] is a sealing material for a display device, comprising an epoxy resin, a thermal acid initiator and a phosphor, wherein the amount of fluorine ions measured by the following test is 100 ppm or less.
[0014] <Experiment>
[0015] A mixture is prepared by combining ingredients other than the phosphor. Next, the mixture is coated on a polyethylene terephthalate film with a thickness of 100 μm and cured to obtain a cured product. Next, the cured product is peeled off from the polyethylene terephthalate film, and the cured product is added to a heat-resistant container made of polytetrafluoroethylene, and 5 mL of ultrapure water is added, and the heat-resistant container is sealed. Next, the heat-resistant container is placed in a dryer and heated at 100°C for 20 hours to obtain an extracted water extracted from the cured product. Next, the heat-resistant container is cooled to 25°C and the extracted water is recovered. Next, after diluting the extracted water, the fluoride ions are quantified by ion chromatography.
[0016] The present invention [2] comprises the sealing material for a display device according to the above [1], wherein the phosphor is a sulfur-containing phosphor.
[0017] The present invention [3] comprises the sealing material for a display device according to the above [1] or [2], wherein the thermal acid initiator contains a fluorine atom.
[0018] The present invention [4] comprises the sealing material for a display device as described in any one of the above [1] to [3], wherein the thermal acid initiator is B(C6F5)4 - It is a quaternary ammonium salt with a counter anion.
[0019] The present invention [5] comprises the sealing material for a display device according to any one of the above [1] to [4], further comprising an antioxidant.
[0020] The present invention [6] comprises the sealing material for a display device according to the above [5], wherein the antioxidant comprises a hindered phenol antioxidant and a phosphite antioxidant.
[0021] The present invention [7] is a sealing material for a display device, which comprises an epoxy resin, a thermal acid initiator and a phosphor, wherein the thermal acid initiator is B(C6F5)4 - It is a quaternary ammonium salt with a counter anion.
[0022] The present invention [8] comprises the sealing material for a display device as described in the above [7], further comprising an antioxidant.
[0023] The present invention [9] comprises the sealing material for a display device according to any one of the above [1] to [8], wherein the color difference in the following color difference test is 1.1 or less.
[0024] Color difference test: The display device sealing material was applied on a glass plate to form a coating film, and then the coating film was heated at 120° C. for 60 minutes to cure the coating film, thereby obtaining a cured product having a thickness of 100 μm.
[0025] Next, a*(initial) was measured for the cured product using a colorimeter. Next, the cured product was stored at 85°C and 85% humidity for 7 days, and a*(after 7 days) was measured. (|a*(initial)|-|a*(after 7 days)|) was taken as the color difference.
[0026] The present invention
[10] includes a sealing member including a cured product of the sealing material for a display device according to any one of the above [1] to [9].
[0027] The present invention
[11] includes an organic EL display comprising the sealing member described in [1] above.
[0028] The present invention
[12] includes an LED display comprising the sealing member described in [1] above.
[0029] Effects of the Invention
[0030] In the sealing material for display device of the present invention, the amount of fluorine ions measured by a predetermined test is 100 ppm or less, or the thermal acid initiator is B(C6F5)4 - It is a quaternary ammonium salt of a counter anion. Therefore, it can suppress the discoloration of the cured product under high temperature and high humidity.
[0031] The sealing member of the present invention includes a cured product of the sealing material for a display device of the present invention, and therefore, discoloration can be suppressed under high temperature and high humidity conditions.
[0032] The organic EL display of the present invention includes the sealing member of the present invention, and thus can suppress discoloration under high temperature and high humidity conditions.
[0033] The LED display of the present invention includes the sealing member of the present invention, and thus can suppress discoloration under high temperature and high humidity conditions. DETAILED DESCRIPTION
[0034] 1. First option
[0035] In a first aspect, a display device sealing material comprises an epoxy resin, a thermal acid initiator, and a phosphor. In addition, in the display device sealing material, an amount of fluorine ions described below is equal to or less than a predetermined value.
[0036] <Epoxy resin>
[0037] Examples of the epoxy resin include an epoxy resin not containing a siloxane skeleton and an epoxy resin containing a siloxane skeleton.
[0038] [Epoxy resin without siloxane skeleton]
[0039] The epoxy resin not containing a siloxane skeleton does not contain a siloxane skeleton and has an epoxy group.
[0040] Examples of the epoxy resin not containing a siloxane skeleton include an aromatic epoxy resin not containing a siloxane skeleton, an alicyclic epoxy resin not containing a siloxane skeleton, and an aliphatic epoxy resin not containing a siloxane skeleton.
[0041] (Aromatic epoxy resin without siloxane skeleton)
[0042] Examples of the aromatic epoxy resin not containing a siloxane skeleton include bisphenol-type epoxy resins (e.g., bisphenol A-type epoxy resins and bisphenol F-type epoxy resins), novolac-type epoxy resins (e.g., phenol novolac-type epoxy resins, cresol novolac-type epoxy resins, and biphenyl novolac-type epoxy resins), and modified products thereof (specifically, alkylene oxide adducts (preferably propylene oxide adducts)).
[0043] As the aromatic epoxy resin not containing a siloxane skeleton, preferably, bisphenol type epoxy resin and / or alkylene oxide adduct of bisphenol type epoxy resin can be mentioned. As the aromatic epoxy resin not containing a siloxane skeleton, more preferably, bisphenol F type epoxy resin and / or propylene oxide adduct of bisphenol A type epoxy resin can be mentioned. As the aromatic epoxy resin not containing a siloxane skeleton, more preferably, bisphenol F type epoxy resin can be mentioned.
[0044] Commercially available aromatic epoxy resins not containing a siloxane skeleton may also be used. Examples of commercially available aromatic epoxy resins not containing a siloxane skeleton include YL983U (bisphenol F epoxy resin, manufactured by Mitsubishi Chemical Corporation) and EP-4010S (propylene oxide adduct of bisphenol A epoxy resin, manufactured by ADEKA Corporation).
[0045] (Alicyclic epoxy resin without siloxane skeleton)
[0046] Examples of the alicyclic epoxy resin not containing a siloxane skeleton include alicyclic epoxy resins not containing a siloxane skeleton and containing a glycidyl group, alicyclic epoxy resins not containing a siloxane skeleton and containing a glycidyl ether group, and epoxy resins not containing a siloxane skeleton and containing an epoxy ring structure.
[0047] ((Alicyclic epoxy resin containing no siloxane skeleton and containing glycidyl group))
[0048] The alicyclic epoxy resin containing no siloxane skeleton and containing a glycidyl group has, for example, a glycidyl group bonded to an aliphatic ring. Such alicyclic epoxy resin containing no siloxane skeleton and containing a glycidyl group is represented by, for example, the following general formula (1).
[0049] [Chemistry 1]
[0050] Chemical 1
[0051]
[0052] In formula (1), R 1 represents a monovalent organic group, and l represents the degree of polymerization. In addition, a substituent such as an alkyl group may be bonded to the carbon atom constituting the cyclohexane ring.
[0053] Specific examples of the alicyclic epoxy resin represented by the general formula (1) that does not contain a siloxane skeleton and contains a glycidyl group include 1,2-epoxy-4-(2-oxiranyl)cyclohexane adducts of 2,2-bis(hydroxymethyl)-1-butanol.
[0054] The alicyclic epoxy resin having no siloxane skeleton and containing a glycidyl group represented by the general formula (1) may be a commercial product. Examples of commercial products of the alicyclic epoxy resin having no siloxane skeleton and containing a glycidyl group represented by the general formula (1) include EHPE3150 (epoxy equivalent 170 to 190 g / eq., manufactured by Daicel Corporation).
[0055] ((Alicyclic epoxy resin containing no siloxane skeleton and containing glycidyl ether group))
[0056] The alicyclic epoxy resin containing no siloxane skeleton and containing a glycidyl ether group has a glycidyl ether unit bonded to an aliphatic ring. Preferably, the alicyclic epoxy resin containing no siloxane skeleton and containing a glycidyl ether group is an alicyclic epoxy resin containing no siloxane skeleton and containing a polyglycidyl ether having a plurality of glycidyl ether units bonded to an aliphatic ring.
[0057] As an alicyclic epoxy resin which does not contain a siloxane skeleton and contains a polyglycidyl ether, an alicyclic epoxy resin which does not contain a siloxane skeleton and contains a difunctional glycidyl ether is mentioned, for example.
[0058] Examples of the alicyclic epoxy resin containing no siloxane skeleton and containing a difunctional glycidyl ether include hydrogenated bisphenol A diglycidyl ether, hydrogenated bisphenol F diglycidyl ether, and hexahydrophthalic acid diglycidyl ether. Preferably, hydrogenated bisphenol A diglycidyl ether is used as the alicyclic epoxy resin containing no siloxane skeleton and containing a difunctional glycidyl ether.
[0059] Commercially available alicyclic epoxy resins containing no siloxane skeleton and containing a glycidyl ether group may also be used. Examples of commercially available alicyclic epoxy resins containing no siloxane skeleton and containing a glycidyl ether group include YX8000 (hydrogenated bisphenol A diglycidyl ether, manufactured by Mitsubishi Chemical Corporation).
[0060] ((Epoxy resin that does not contain a siloxane skeleton and contains an epoxy ring structure))
[0061] The epoxy resin containing no siloxane skeleton and containing an epoxy ring structure has an epoxy ring structure having an epoxy group composed of two adjacent carbon atoms forming an aliphatic ring and one oxygen atom bonded to the two carbon atoms.
[0062] Examples of the epoxy resin containing no siloxane skeleton and containing an epoxy ring structure include epoxy resin containing no siloxane skeleton and containing an epoxycyclohexane structure (hereinafter referred to as an ECH structure-containing epoxy resin).
[0063] Examples of epoxy resins containing an ECH structure include an epoxy resin containing one ECH structure represented by the following chemical formula (2), an epoxy resin containing one ECH structure represented by the following chemical formula (3), an epoxy resin containing two ECH structures represented by the following general formula (4), and modified products thereof.
[0064] [Chemistry 2]
[0065] Chemical 2
[0066]
[0067] [Chemistry 3]
[0068] Chemical 3
[0069]
[0070] [Chemistry 4]
[0071] Chemical 4
[0072]
[0073] In formula (4), X represents a linking group (a divalent group having one or more atoms). 2 represents an atom or a substituent selected from the group consisting of a hydrogen atom, a fluorine atom, an alkyl group, a fluoroalkyl group, an aryl group, a furyl group, and a thienyl group. 2 They can be the same as or different from each other.
[0074] The epoxy resin containing two ECH structures represented by the general formula (4) (hereinafter referred to as the epoxy resin containing an ECH structure represented by the general formula (4)) has an ECH structure (epoxycyclohexyl group) at both ends of the molecule, and the two epoxycyclohexyl groups are bonded via a connecting group. It should be noted that the epoxycyclohexyl group is a functional group containing a cyclohexane ring and an epoxy group, and the epoxy group is composed of two adjacent carbon atoms forming a cyclohexane ring and one oxygen atom bonded to the two carbon atoms.
[0075] In the above general formula (4), R 2Examples of the alkyl group include linear or branched alkyl groups having 1 to 6 carbon atoms (e.g., methyl, ethyl, propyl, butyl, pentyl, and hexyl).
[0076] In the above general formula (4), R 2 Examples of the fluoroalkyl group include linear or branched fluoroalkyl groups having 1 to 6 carbon atoms (eg, perfluoromethyl, perfluoroethyl, and perfluoropropyl).
[0077] In the above general formula (4), as R 2 Examples of the aryl group include aryl groups having 6 to 18 carbon atoms (for example, phenyl and naphthyl).
[0078] In the above general formula (4), examples of the linking group represented by X include oxygen atoms, sulfur atoms, divalent hydrocarbon groups, polyoxyalkylene groups, carbonyl groups, ether groups, thioether groups, ester groups, carbonate groups, amide groups, and groups formed by linking these groups.
[0079] Examples of the divalent hydrocarbon group include a linear or branched alkylene group having 1 to 20 carbon atoms (e.g., methylene, methylmethylene, dimethylmethylene, ethylene, propylene, trimethylene, and butylene), and a linear or branched unsaturated hydrocarbon group having 1 to 20 carbon atoms (e.g., propenylene, methylpropenylene, and butenylene).
[0080] Examples of the polyoxyalkylene group include linear or branched polyoxyalkylene groups having 1 to 120 carbon atoms (eg, a polyoxyethylene group and a polyoxypropylene group).
[0081] Specific examples of the epoxy resin containing an ECH structure represented by the general formula (4) include (3,3',4,4'-diepoxy)bicyclohexane, bis(3,4-epoxycyclohexylmethyl)ether, 1,2-bis(3,4-epoxycyclohexane-1-yl)ethane, 2,2-bis(3,4-epoxycyclohexane-1-yl)propane, 3',4'-epoxycyclohexylmethyl(3,4-epoxy)cyclohexanecarboxylate, and ε-caprolactone-modified 3',4'-epoxycyclohexylmethyl3,4-epoxycyclohexanecarboxylate. Preferred examples of the epoxy resin containing an ECH structure represented by the general formula (4) include 3',4'-epoxycyclohexylmethyl(3,4-epoxy)cyclohexanecarboxylate.
[0082] In addition, the epoxy resin containing the ECH structure represented by the general formula (4) may be a commercial product. Examples of commercial products of the epoxy resin containing the ECH structure represented by the general formula (4) include CELLOXIDE 2021P (3',4'-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate) (both manufactured by Daicel Corporation).
[0083] Preferred examples of the ECH structure-containing epoxy resin include the ECH structure-containing epoxy resin represented by the above-mentioned general formula (4).
[0084] Furthermore, as the alicyclic epoxy resin not containing a siloxane skeleton, preferably, there can be mentioned an alicyclic epoxy resin not containing a siloxane skeleton and containing a glycidyl ether group and / or an epoxy resin not containing a siloxane skeleton and containing an epoxy ring structure.
[0085] (Aliphatic epoxy resin without siloxane skeleton)
[0086] Examples of the aliphatic epoxy resin not containing a siloxane skeleton include bifunctional aliphatic epoxy resins not containing a siloxane skeleton, and examples of the bifunctional aliphatic epoxy resin not containing a siloxane skeleton include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and neopentyl glycol diglycidyl ether.
[0087] Examples of the epoxy resin not containing a siloxane skeleton include aromatic epoxy resins not containing a siloxane skeleton and / or alicyclic epoxy resins not containing a siloxane skeleton.
[0088] [Epoxy resin containing siloxane skeleton]
[0089] The epoxy resin containing a siloxane skeleton has both a siloxane skeleton and an epoxy group.
[0090] As an epoxy resin containing a siloxane skeleton, the epoxy resin containing a linear siloxane skeleton, the epoxy resin containing a cyclic siloxane skeleton, and the epoxy resin containing a ladder siloxane skeleton are mentioned, for example.
[0091] (Epoxy resin containing a linear siloxane skeleton)
[0092] The epoxy resin containing a linear siloxane skeleton is, for example, a compound represented by the following formula (5).
[0093] [Chemistry 5]
[0094] Chemical 5
[0095]
[0096] In the above formula (5), m represents an integer greater than 1 and less than 20. In addition, in the above formula (5), n represents an integer greater than 1 and less than 10. In addition, in the above formula (5), o represents an integer greater than 1 and less than 10. In the above formula (5), Y represents an epoxy group or an epoxycyclic group (e.g., an epoxycyclohexyl group). In addition, in the above formula (5), two Ys are the same or different from each other.
[0097] Preferred examples of the epoxy resin containing a linear siloxane skeleton include compounds represented by the following formula (6) (a compound in which, in the above formula (5), m represents 1, n represents 2, o represents 2, and two Ys represent cyclohexyl oxide groups).
[0098] [Chemistry 6]
[0099] Chemical 6
[0100]
[0101] In addition, a commercially available epoxy resin containing a linear siloxane skeleton may be used. Examples of commercially available epoxy resin containing a linear siloxane skeleton include X-40-2669 (a compound represented by the above formula (6), manufactured by Shin-Etsu Chemical Co., Ltd.).
[0102] (Epoxy resin containing cyclic siloxane skeleton)
[0103] The cyclic siloxane skeleton-containing epoxy resin has a cyclic siloxane skeleton.
[0104] Examples of the cyclic siloxane skeleton include a hexamethylcyclotrisiloxane skeleton (C6H 18 O3Si3), octamethylcyclotetrasiloxane skeleton (C8H 24 O4Si4), and decamethylcyclopentasiloxane skeleton (C 10 H 30 O5Si5).
[0105] The epoxy resin containing a cyclic siloxane skeleton preferably has an octamethylcyclotetrasiloxane skeleton.
[0106] Such an epoxy resin containing a cyclic siloxane skeleton is, for example, a compound represented by the following formula (7).
[0107] [Chemistry 7]
[0108] Chemical 7
[0109]
[0110] In the above formula (7), Z represents a linking group (a divalent group having one or more atoms). Examples of the linking group include an alkylene group having 1 to 8 carbon atoms. Examples of the alkylene group having 1 to 8 carbon atoms include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, a hexylene group, a heptylene group, and an octylene group.
[0111] In the above formula (7), Y has the same meaning as Y in the above formula (5).
[0112] In the above formula (7), R 3represents a saturated hydrocarbon group or -ZY. Examples of the saturated hydrocarbon group include a linear or branched alkyl group having 1 to 6 carbon atoms and a cycloalkyl group having 3 to 6 carbon atoms. Examples of the linear or branched alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, and a hexyl group. Examples of the cycloalkyl group having 3 to 6 carbon atoms include a cyclopentyl group and a cyclohexyl group. In the above formula (7), the six R 3 The same or different from each other.
[0113] Preferred examples of the epoxy resin containing a cyclic siloxane skeleton include a compound represented by the following formula (8) and / or a compound represented by the following formula (9).
[0114] [Chemistry 8]
[0115] Chemical 8
[0116]
[0117] [Chemistry 9]
[0118] Chemical 9
[0119]
[0120] In addition, commercial products of epoxy resins containing cyclic siloxane skeletons may also be used. Commercial products of epoxy resins containing cyclic siloxane skeletons include, for example, X-40-2678 (a compound represented by the above formula (8), manufactured by Shin-Etsu Chemical Co., Ltd.) and KR-470 (a compound represented by the above formula (9), manufactured by Shin-Etsu Chemical Co., Ltd.).
[0121] (Epoxy resin containing ladder siloxane skeleton)
[0122] The epoxy resin containing a ladder siloxane skeleton contains a ladder siloxane skeleton.
[0123] As shown in the following formula (10), the ladder siloxane skeleton is a two-dimensional network structure in which siloxane bonds have a ladder-like skeleton.
[0124] [Chemistry 10]
[0125] Chemical 10
[0126]
[0127] Examples of the epoxy resin containing a ladder siloxane skeleton include compounds represented by the following formula (11).
[0128] [Chemistry 11]
[0129] Chemical 11
[0130]
[0131] Moreover, a commercial item of the epoxy resin containing a ladder siloxane skeleton may be used. As a commercial item of the epoxy resin containing a ladder siloxane skeleton, YL-9028 (compound represented by the above formula (10), manufactured by Mitsubishi Chemical Corporation) is mentioned, for example.
[0132] The weight average molecular weight of the epoxy resin is, for example, not less than 130 and not more than 3000. The weight average molecular weight (Mw) can be determined by gel permeation chromatography (GPC) using polystyrene as a standard substance.
[0133] The epoxy equivalent in the epoxy resin is, for example, 100 g / eq. or more, and for example, 1000 g / eq. or less. The epoxy equivalent can be measured in accordance with JIS K7236:2001.
[0134] The epoxy resins can be used alone or in combination of two or more.
[0135] The content ratio of the epoxy resin with respect to the display device sealing material is, for example, 20 mass % or more, preferably 30 mass % or more, and, for example, 60 mass % or less.
[0136] <Thermal Acid Initiator>
[0137] The thermal acid initiator is a thermal acid generator that generates an acid by heat.
[0138] The thermal acid initiator contains fluorine atoms and is selected so that the amount of fluorine ions described below becomes equal to or less than a predetermined value.
[0139] As such a thermal acid initiator, for example, B(C6F5)4 - It is a quaternary ammonium salt with a counter anion.
[0140] In addition, a commercially available thermal acid initiator may also be used. Examples of commercially available thermal acid initiators include CXC-1821 (based on B(C6F5)4 - It is a quaternary ammonium salt of counter anion, manufactured by King Industry Co., Ltd.).
[0141] The thermal acid initiator can be used alone or in combination of two or more.
[0142] The content ratio of the thermal acid initiator relative to 100 parts by mass of the epoxy resin is, for example, 1 part by mass or more, for example, 10 parts by mass or less, and preferably 5 parts by mass or less.
[0143] The content ratio of the thermal acid initiator with respect to the display device sealing material is, for example, 0.5 mass % or more, for example, 5 mass % or less, and preferably 2.5 mass % or less.
[0144] <Phosphor>
[0145] The phosphor has a wavelength conversion function. For example, the phosphor converts light from an optical element into light of a predetermined wavelength.
[0146] Examples of the phosphor include a sulfur-containing phosphor and a sulfur-free phosphor.
[0147] Examples of the sulfur-containing phosphor include a sulfur-containing red phosphor, a sulfur-containing green phosphor, a sulfur-containing blue phosphor, and a sulfur-containing yellow phosphor.
[0148] Examples of the sulfur-containing red phosphor include (Ca, Sr)S:Eu, (Zn, Cd)(S, Se):Ag, Ba2ZnS3:Mn, (Ca 1-x Sr x )S:Eu,In (0 < x < 1) and La2O2S:Eu.
[0149] Examples of the sulfur-containing green phosphor include (Ca, Sr, Ba)(Al, Ga, In)2S4:Eu, SrS:Tb, and CaS:Ce.
[0150] Examples of the sulfur-containing blue phosphor include SrS:Ce, (Sr, Ca)Ga2S4:Ce, BaAl2S4:Eu, Ba2SiS4:Ce, Ba2(Si 1-x Al x )S4:Ce (0 < x < 1).
[0151] Examples of the sulfur-containing yellow phosphor include CaGa2S4:Eu, Sr2SiS4:Eu, and CaS:Ce,Eu.
[0152] Examples of the sulfur-free phosphor include a sulfur-free yellow phosphor and a sulfur-free red phosphor.
[0153] Examples of the sulfur-free yellow phosphor include Y3Al5O 12 :Ce and Tb3Al3O 12 :Ce.
[0154] Examples of the sulfur-free red phosphor include CaAlSiN3:Eu and CaSiN2:Eu.
[0155] As the phosphor, from the viewpoint of improving color purity, sulfur-containing phosphors are preferably used. As the phosphor, sulfur-containing green phosphors are more preferably used.
[0156] The phosphor can be used alone or in combination of two or more.
[0157] The content ratio of the phosphor relative to components other than the phosphor (specifically, epoxy resin, thermal acid initiator and other components mixed as needed (described later)) is, for example, 60 parts by mass or more, preferably 80 parts by mass or more, and, for example, 150 parts by mass or less, preferably 120 parts by mass or less.
[0158] The content ratio of the phosphor relative to 100 parts by mass of the epoxy resin is, for example, 40 parts by mass or more, preferably 80 parts by mass or more, and, for example, 250 parts by mass or less, preferably 180 parts by mass or less, and more preferably 130 parts by mass or less.
[0159] The content ratio of the fluorescent body with respect to the display device sealing material is, for example, 40 mass % or more, and for example, 60 mass % or less.
[0160] <Other ingredients>
[0161] The display device sealing material may contain other components as necessary.
[0162] Examples of other components include other cationic polymerizable compounds and additives.
[0163] [Other cationic polymer compounds]
[0164] Other cationically polymerizable compounds are cationically polymerizable compounds other than epoxy resins, and examples thereof include oxetane compounds.
[0165] The oxetane compound contains, for example, 1 to 5 oxetane rings.
[0166] Examples of the oxetane compound include a monofunctional oxetane compound having one oxetane ring, a difunctional oxetane compound having two oxetane rings, and a trifunctional or higher functional oxetane compound having three or more oxetane rings.
[0167] Examples of the monofunctional oxetane compound include 2-ethylhexyloxetane, 3-ethyl-3-hydroxymethyloxetane, 3-(methyl)allyloxymethyl-3-ethyloxetane, (3-ethyl-3-oxetanylmethoxy)methylbenzene, 2-ethylhexyl (3-ethyl-3-oxetanylmethyl) ether, ethyldiethylene glycol (3-ethyl-3-oxetanylmethyl) ether, and 3-cyclohexylmethyl-3-ethyloxetane.
[0168] Examples of the difunctional oxetane compound include 1,4-bis{[(3-ethyl-3-oxetanyl)methoxy]methyl}benzene, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, 1,4-bis[(3-ethyl-3-oxetanyl)methoxy]benzene, 1,3-bis[(3-ethyl-3-oxetanyl)methoxy]benzene, 3,7-bis(3- [(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, and dicyclopentenylbis(3-ethyl-3-oxetanylmethyl)ether. As the difunctional oxetane compound, preferably 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane can be used.
[0169] Commercially available difunctional oxetane compounds may also be used. Examples of commercially available difunctional oxetane compounds include ARON OXETANE OXT-221 (3-ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, manufactured by Toagosei Chemical Co., Ltd.).
[0170] Examples of trifunctional or higher-functional oxetane compounds include trimethylolpropane tris(3-ethyl-3-oxetanylmethyl)ether, pentaerythritol tris(3-ethyl-3-oxetanylmethyl)ether, pentaerythritol tetrakis(3-ethyl-3-oxetanylmethyl)ether, and dipentaerythritol penta(3-ethyl-3-oxetanylmethyl)ether.
[0171] As the oxetane compound, preferably a bifunctional oxetane compound is used.
[0172] Other cationic polymerizable compounds may be used alone or in combination of two or more.
[0173] The content ratio of other cationic polymerizable compounds relative to 100 parts by mass of the epoxy resin is, for example, 60 parts by mass or more, preferably 80 parts by mass or more, and, for example, 150 parts by mass or less, preferably 120 parts by mass or less.
[0174] The content ratio of the other cationic polymerizable compound relative to the display device sealing material is, for example, 10 mass % or more, and, for example, 30 mass % or less.
[0175] [additive]
[0176] As additives, for example, tackifiers, photosensitizers, leveling agents, coupling agents, light stabilizers, antioxidants, polymerization initiation aids, anti-aging agents, wettability improvers, surfactants, plasticizers, ultraviolet absorbers, preservatives and antibacterial agents can be mentioned. As additives, from the viewpoint of further suppressing the discoloration of the cured product under high temperature and high humidity, preferably light stabilizers and / or antioxidants can be mentioned. The additives can be used alone or in combination of two or more.
[0177] Examples of the light stabilizer include hindered amine light stabilizers. Examples of the hindered amine light stabilizer include tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)1,2,3,4-butanetetracarboxylate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)1,2,3,4-butanetetracarboxylate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-undecanyloxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate, 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate, and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate. As the light stabilizer, preferably, bis(1-undecyoxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate is used.
[0178] A commercially available light stabilizer may be used. Examples of commercially available light stabilizers include ADK STAB LA-81 (bis(1-undecanyloxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate, manufactured by ADEKA Corporation).
[0179] The light stabilizers may be used alone or in combination of two or more.
[0180] The content ratio of the light stabilizer relative to 100 parts by mass of the epoxy resin is, for example, 0.1 parts by mass or more, preferably 0.5 parts by mass or more, and, for example, 5 parts by mass or less, preferably 2 parts by mass or less.
[0181] The content ratio of the light stabilizer relative to the display device sealing material is, for example, 0.05 mass % or more, preferably 0.25 mass % or more, and, for example, 2.5 mass % or less, preferably 1 mass % or less.
[0182] Examples of the antioxidant include hindered phenol antioxidants and phosphite antioxidants.
[0183] Examples of the hindered phenol antioxidant include 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,1,3-tris-(2'-methyl-4'-hydroxy-5'-tert-butylphenyl)-butane, stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 3,9-bis[2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane. As the hindered phenol antioxidant, preferably, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is used.
[0184] Examples of the phosphite antioxidant include tris(2-ethylhexyl) phosphite, isodecyl diphenyl phosphite, trilauryl phosphite, tritridecyl phosphite, and tristearyl phosphite. Preferably, the phosphite antioxidant includes decyl diphenyl isophosphite.
[0185] The content ratio of the antioxidant relative to 100 parts by mass of the epoxy resin is, for example, 1 part by mass or more, and for example, 10 parts by mass or less, and preferably 5 parts by mass or less.
[0186] The content ratio of the antioxidant relative to the display device sealing material is, for example, 0.5 mass % or more, and for example, 5 mass % or less, and preferably 2.5 mass % or less.
[0187] The antioxidant may be used alone or in combination of two or more. From the viewpoint of further suppressing discoloration of the cured product under high temperature and high humidity, it is preferred to use a hindered phenol antioxidant and a phosphite antioxidant in combination.
[0188] When a hindered phenol antioxidant and a phosphite antioxidant are used together as the antioxidant, the content ratio of the hindered phenol antioxidant is, for example, 30 parts by mass or more, preferably 40 parts by mass or more, and for example, 70 parts by mass or less, preferably 60 parts by mass or less, relative to 100 parts by mass of the total amount of the hindered phenol antioxidant and the phosphite antioxidant. In addition, the content ratio of the phosphite antioxidant is, for example, 30 parts by mass or more, preferably 40 parts by mass or more, and for example, 70 parts by mass or less, preferably 60 parts by mass or less, relative to 100 parts by mass of the total amount of the hindered phenol antioxidant and the phosphite antioxidant.
[0189] <Preparation of Sealing Material for Display Device>
[0190] In order to prepare the sealing material for a display device, an epoxy resin, a thermal acid initiator, a phosphor, and other components as needed are mixed.
[0191] Specifically, first, an epoxy resin, a thermal acid initiator, and other components as needed are mixed to prepare a mixture.
[0192] Next, the mixture is mixed with a phosphor, thereby preparing a sealing material for a display device.
[0193] The display device sealing material may be diluted with a known solvent to form a varnish. In this case, the solid content concentration of the display device sealing material varnish is, for example, 10% by mass or more and, for example, 70% by mass or less.
[0194] The amount of fluorine ions in the display device sealing material measured by a test described later is 100 ppm or less, preferably 50 ppm or less, more preferably 20 ppm or less, and usually 1 ppm or more.
[0195] In detail, in the test, a mixture is prepared by combining ingredients other than the phosphor. Then, a 100 μm thick mixture is applied on a polyethylene terephthalate film using an auxiliary device, and the mixture is cured to obtain a cured product. Then, the cured product is peeled off from the polyethylene terephthalate film, and the cured product is added to a heat-resistant container made of polytetrafluoroethylene, and 5 mL of ultrapure water is added at the same time, and the heat-resistant container is sealed. Then, the heat-resistant container is placed in a dryer and heated at 100°C for 20 hours to obtain an extracted water extracted from the cured product. Then, the heat-resistant container is cooled to 25°C and the extracted water is recovered. Then, after diluting the extracted water, fluoride ions are quantified for the extracted water using ion chromatography.
[0196] When the amount of the fluorine ions is not more than the upper limit, discoloration of the cured product can be suppressed under high temperature and high humidity conditions.
[0197] When the amount of the fluorine ions exceeds the upper limit, discoloration of the cured product cannot be suppressed under high temperature and high humidity.
[0198] In addition, in the sealing material for display devices, the color difference measured by the color difference test described later is, for example, 5.0 or less, preferably 4.0 or less, more preferably 3.0 or less, further preferably 2.0 or less, and particularly preferably 1.1 or less from the viewpoint of further suppressing discoloration of the cured product.
[0199] Furthermore, such a sealing material for a display device can suppress discoloration of a cured product under high temperature and high humidity conditions and therefore can be suitably used as a sealing material for sealing an optical element.
[0200] <Seal>
[0201] The sealing member includes a cured product of the above-mentioned sealing material for a display device.
[0202] In order to cure the display device sealing material, the display device sealing material is heated.
[0203] As heating conditions, the heating temperature is, for example, 60° C. or higher, preferably 100° C. or higher, and for example, 150° C. or lower. The heating time is, for example, 1 minute or higher, preferably 30 minutes or higher, and for example, 120 minutes or lower.
[0204] Thereby, the display device sealing material is cured to obtain a cured product of the display device sealing material.
[0205] The cured product of the sealing material for display devices preferably has transparency. Specifically, the total light transmittance (according to JIS K 7361-1) of the cured product of the sealing material for display devices is, for example, 80% or more, preferably 85% or more, more preferably 90% or more, further preferably 95% or more, and, for example, 100% or less.
[0206] Furthermore, such a sealing member can be suitably used in the manufacture of organic EL displays and LED displays.
[0207] That is, the organic EL display comprises an organic EL element and a sealant. Specifically, the organic EL display comprises an organic EL element and a sealant covering the surface of the organic EL element. In addition, the LED display comprises an LED and a sealant. Specifically, the LED display comprises an LED and a sealant covering the surface of the LED.
[0208] 2. Second Option
[0209] In the second embodiment, the sealing material for display device comprises epoxy resin, thermal acid initiator and phosphor. In addition, the thermal acid initiator is B(C6F5)4 - It is a quaternary ammonium salt with a counter anion.
[0210] The sealing material for display device comprises B(C6F5)4 - The quaternary ammonium salt of the counter anion is a thermal acid initiator, so it can suppress the discoloration of the cured product under high temperature and high humidity.
[0211] The content of the thermal acid initiator is the same as that of the thermal acid initiator in the first embodiment.
[0212] The epoxy resin and the phosphor are the same as the epoxy resin and the thermal acid initiator exemplified in the first embodiment. The content ratios thereof are the same as the content ratios exemplified in the first embodiment.
[0213] The display device sealing material may contain other components listed in the first embodiment as necessary. The content ratios thereof are the same as those listed in the first embodiment.
[0214] Moreover, the display device sealing material can be prepared by the same method as the first embodiment. In addition, by curing the display device sealing material using the same method as the first embodiment, a cured product (sealing member) of the display device sealing material that is the same as the first embodiment can be manufactured. In addition, using the sealing member, an organic EL display and an LED display that are the same as the first embodiment can be manufactured.
[0215] 3. Effect
[0216] In the sealing material for display device, the amount of fluorine ions measured by a predetermined test is 100 ppm or less, or in the sealing material for display device, the thermal acid initiator is B(C6F5)4 - It is a quaternary ammonium salt of a counter anion. Therefore, it can suppress the discoloration of the cured product under high temperature and high humidity.
[0217] Specifically, a cured product of a sealing material for a display device including a phosphor has a problem of discoloration due to fluorine ions generated from a thermal acid initiator under high temperature and high humidity.
[0218] In particular, from the viewpoint of improving heat resistance, water resistance, and adhesiveness, epoxy resin is selected over silicone resin. However, when epoxy resin is selected, the above-mentioned discoloration is likely to occur.
[0219] On the other hand, in the sealing material for display device, the amount of fluorine ions measured by a predetermined test is less than 100 ppm, or, in the sealing material for display device, the thermal acid initiator is B(C6F5)4 - Since it is a quaternary ammonium salt of a counter anion, the amount of fluoride ions generated by the thermal acid initiator is suppressed. Therefore, even if an epoxy resin is included, discoloration of the cured product can be suppressed under high temperature and high humidity.
[0220] Example
[0221] Next, the present invention will be described based on examples and comparative examples, but the present invention is not limited to the following examples. In addition, "parts" and "%" are mass references unless otherwise specified. In addition, the specific numerical values such as the mixing ratio (containing ratio), physical property values, parameters, etc. used in the following descriptions can replace the upper limit values (defined as "below", "lower than") or lower limits (defined as "above", "exceeding") of the corresponding mixing ratios (containing ratios), physical property values, parameters, etc. recorded in the above-mentioned "Specific Implementation Methods" and corresponding to them.
[0222] <Details of ingredients>
[0223] The trade names and abbreviations of the components used in each Example and each Comparative Example are described in detail.
[0224] YL983U: Bisphenol F epoxy resin, manufactured by Mitsubishi Chemical Corporation
[0225] EP-4010S: Propylene oxide adduct of bisphenol A epoxy resin, manufactured by ADEKA Co., Ltd.
[0226] YX8000: Hydrogenated bisphenol A diglycidyl ether, manufactured by Mitsubishi Chemical Corporation
[0227] CEL2021P: 3',4'-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate, an epoxy resin having an ECH structure represented by the above general formula (4), trade name "CELLOXIDE 2021P", epoxy equivalent: 128 to 145 g / eq., manufactured by Daicel Corporation
[0228] X-40-2669: Epoxy resin containing a linear siloxane skeleton (compound represented by the above formula (6)), manufactured by Shin-Etsu Chemical Co., Ltd.
[0229] X-40-2678: Epoxy resin containing a cyclic siloxane skeleton (the compound represented by the above formula (8)), manufactured by Shin-Etsu Chemical Co., Ltd.
[0230] KR-470: cyclic siloxane skeleton-containing epoxy resin (compound represented by the above formula (9)), manufactured by Shin-Etsu Chemical Co., Ltd.
[0231] YL-9028: an epoxy resin containing a ladder siloxane skeleton (a compound represented by the above formula (10)), manufactured by Mitsubishi Chemical Corporation
[0232] CXC-1821: B(C6F5)4 - Quaternary ammonium salts to counteract anions, manufactured by King Industry
[0233] CXC-1733: SbF6 - Quaternary ammonium salt for counter anion, manufactured by King Industry
[0234] OXT-221: 3-ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, trade name "ARON OXETANE OXT-221", manufactured by Toa Gosei Chemical Co., Ltd.
[0235] LA-81: Bis(1-undecyloxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate, trade name "ADK STABLA-81", manufactured by ADEKA Corporation
[0236] AO-60: Hindered phenol antioxidant (pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), manufactured by ADEKA
[0237] 135A: Phosphite antioxidant (isodecyl diphenyl phosphite), manufactured by ADEKA
[0238] <Preparation of Sealing Material for Display Device>
[0239] Examples 1 to 13 and Comparative Examples 1 to 5
[0240] Based on the formulations described in Tables 1 and 2, the epoxy resin, the thermal acid initiator, and other components were mixed using a magnetic stirrer to prepare a mixture.
[0241] Next, the mixture and the phosphor (sulfur-containing phosphor) were mixed in a ratio of mixture / phosphor = 1 / 1 (mass ratio), and mixed by V-Mini 300 manufactured by EME at 1600 revolutions for 1 minute. Thus, a sealing material for a display device was prepared. It should be noted that the numerical values of the components described in Tables 1 and 2 are in parts by mass.
[0242] <Evaluation>
[0243] [Amount of fluoride ions]
[0244] Based on the formula of each embodiment and each comparative example, a mixture containing ingredients other than the phosphor is prepared. Then, the above mixture (a mixture consisting of ingredients other than the phosphor) is applied to a polyethylene terephthalate film with a thickness of 100 μm using an applicator, and the mixture is cured to obtain a cured product. Then, the cured product is peeled off from the polyethylene terephthalate film, and the cured product is added to a heat-resistant container made of polytetrafluoroethylene, and 5 mL of ultrapure water is added at the same time, and the heat-resistant container is sealed. Then, the heat-resistant container is placed in a dryer and heated at 100°C for 20 hours to obtain the extracted water extracted from the cured product. Then, the heat-resistant container is cooled to 25°C and the extracted water is recovered. Then, after diluting the extracted water, the fluoride ions are quantified for the extracted water using ion chromatography (measurement device: ICS-3000 (manufactured by Thermo Fisher Scientific)). The results are shown in Tables 1 and 2.
[0245] [Color difference test]
[0246] The sealing material for a display device of each example and each comparative example was applied on a glass plate to form a coating film, and then the coating film was heated at 120° C. for 60 minutes to cure the coating film, thereby obtaining a cured product (thickness 100 μm).
[0247] Next, the cured product was measured using a colorimeter (SE2000, manufactured by Nippon Denshoku Industries, Ltd.) * (initial). Next, the cured product was stored at 85°C and 85% humidity for 2 days. Next, the a * (After 2 days). Then, the solidified product was further stored at 85°C and 85% humidity for 5 days. Then, based on the same procedure, a * (After 7 days). It can be seen that the color difference (|a * (initial)|-|a * The smaller the (after 7 days)|), the more discoloration can be suppressed under high temperature and high humidity. The results are shown in Tables 1 and 2.
[0248] <Inspection>
[0249] Examples 1 to 13 in which the amount of fluorine ions is 100 ppm or less have smaller color differences than Comparative Examples 1 to 5 in which the amount of fluorine ions exceeds 100 ppm. This shows that if the amount of fluorine ions is 100 ppm or less, discoloration can be suppressed under high temperature and high humidity conditions.
[0250] [Table 1]
[0251] Table 1
[0252] [Table 2]
[0253] Table 2
[0254]
[0255] It should be noted that the above-mentioned embodiments are provided as exemplary embodiments of the present invention, but these are merely exemplary and should not be construed in a limiting sense. Modifications of the present invention that are obvious to those skilled in the art are within the scope of the following claims.
[0256] Possibility of Industrial Application
[0257] The sealing material and sealing member for display devices of the present invention are preferably used for, for example, organic EL displays and LED displays. The organic EL displays and LED displays of the present invention are preferably used for the production of display devices.
Claims
1. A sealing material for a display device, comprising an epoxy resin, a thermal acid initiator and a phosphor, wherein the amount of fluoride ions measured by the following test is 100 ppm or less, <Experiment> A mixture is prepared by adding ingredients other than the phosphor; then, the mixture is coated on a polyethylene terephthalate film to a thickness of 100 μm and cured to obtain a cured product; then, the cured product is peeled off from the polyethylene terephthalate film, the cured product is added to a heat-resistant container made of polytetrafluoroethylene, 5 mL of ultrapure water is added, and the heat-resistant container is sealed; then, the heat-resistant container is placed in a dryer and heated at 100°C for 20 hours to obtain an extract water extracted from the cured product; then, the heat-resistant container is cooled to 25°C and the extract water is recovered; then, after diluting the extract water, fluoride ions are quantified by ion chromatography.
2. The sealing material for a display device according to claim 1, wherein The phosphor is a sulfur-containing phosphor.
3. The sealing material for a display device according to claim 1, wherein The thermal acid initiator contains fluorine atoms.
4. The sealing material for a display device according to claim 1, wherein The thermal acid initiator is B(C6F5)4 - It is a quaternary ammonium salt with a counter anion. The sealing material for a display device according to claim 1 , further comprising an antioxidant.
6. The sealing material for a display device according to claim 5, wherein The antioxidant comprises a hindered phenol antioxidant and a phosphite antioxidant.
7. A sealing material for a display device, comprising an epoxy resin, a thermal acid initiator and a phosphor, wherein the thermal acid initiator is a B(C6F5)4 - It is a quaternary ammonium salt with a counter anion. The sealing material for a display device according to claim 7 , further comprising an antioxidant.
9. The sealing material for a display device according to claim 1, wherein the color difference in the following color difference test is 1.1 or less, Color difference test: The sealing material for the display device is applied on a glass plate to form a coating film; then, the coating film is heated at 120°C for 60 minutes to cure the coating film to obtain a cured product with a thickness of 100 μm; then, the initial a* of the cured product is measured using a colorimeter; then, the cured product is stored at 85°C and 85% humidity for 7 days, and the a* after 7 days is measured; (|initial a*|-|a* after 7 days|) is taken as the color difference. 10 . A sealing member comprising a cured product of the sealing material for a display device according to claim 1 . 11 . An organic EL display comprising the sealing member according to claim 1 . 12 . An LED display comprising the sealing member according to claim 1 .
Citation Information
Patent Citations
Image display apparatus sealing material
WO2021024616A1